Microwave assisted low temperature rapid synthesis of manganite system using La0.67Ce0.03Sr0.3MnO3 mini-cavity furnace - Kale, Sangeeta N.; Rajagopal, Rajashree; Mona, J.; Londhe, D. P.; Joshi, Rakesh S.; Jagadale, Tushar C.; Satyanarayana, C.; Ravi, V. (Materials Letters, 2008)
Amorphous La0.7Sr0.3MnO3 (LSMO) and La0.7Ca0.3MnO3 (LCMO) precursor powders synthesized by the citrate gel method at 673 K, have been found to crystallize by microwave irradiation in just 60 s using La0.67Ce0.03Sr0.3MnO3 (Ce-LSMO) as couplant. This is the lowest temperature treatment and synthesis time so far reported in literature for the fort-nation of manganite systems. Using ceramic route, the same amorphous samples crystallize on heat treatment only at temperatures greater than 1000 K. The microwave heating through this method is novel and has tremendous potential for accelerating the evolution of the product phase in very shorter durations, with just low temperature processing of the precursors, which cannot be realized in normal process. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Citrate gel method; LSMO; Manganites; Microwave; Oxides

Molecular investigations of protriptyline as a multi-target directed ligand in alzheimer's disease - Bansode, Sneha B.; Jana, Asis K.; Batkulwar, Kedar B.; Warkad, Shrikant D.; Joshi, Rakesh S.; Sengupta, Neelanjana; Kulkarni, Mahesh J. (Plos One, 2014)
Alzheimer's disease (AD) is a complex neurodegenerative disorder involving multiple cellular and molecular processes. The discovery of drug molecules capable of targeting multiple factors involved in AD pathogenesis would greatly facilitate in improving therapeutic strategies. The repositioning of existing non-toxic drugs could dramatically reduce the time and costs involved in developmental and clinical trial stages. In this study, preliminary screening of 140 FDA approved nervous system drugs by docking suggested the viability of the tricyclic group of antidepressants against three major AD targets, viz. Acetylcholinesterase (AChE), beta-secretase (BACE-1), and amyloid beta (A beta) aggregation, with one member, protriptyline, showing highest inhibitory activity. Detailed biophysical assays, together with isothermal calorimetry, fluorescence quenching experiments, kinetic studies and atomic force microscopy established the strong inhibitory activity of protriptyline against all three major targets. The molecular basis of inhibition was supported with comprehensive molecular dynamics simulations. Further, the drug inhibited glycation induced amyloid aggregation, another important causal factor in AD progression. This study has led to the discovery of protriptyline as a potent multi target directed ligand and established its viability as a promising candidate for AD treatment.

Molecular determinant for specificity: differential interaction of alpha-amylases with their proteinaceous inhibitors - Rane, Ashwini S.; Joshi, Rakesh S.; Giri, Ashok P. (Biochimica Et Biophysica Acta-General Subjects, 2020)
Background: alpha-Amylase inhibitors (alpha-AIs) belong to the discrete classes, and exhibited differential specificities against alpha-amylases from various sources. Several alpha-amylases and their complexes with inhibitors at the molecular level have been studied in detail. Interestingly, some alpha-AIs depict specific and selective interactions amid different insect alpha-amylases. Scope of review: There are studies to understand evolutionary variability and functional differentiation of insect alpha-amylases and their cognate inhibitors. We have examined sequence, structural, and interaction diversity between various alpha-amylases and alpha-AIs. Based on these analyses, we are providing a potential basis for the functional differentiation among certain insect a-amylases concerning mammalian counterparts and their interactions with different proteinaceous alpha-AIs. Major conclusions: Insect alpha-amylases have conserved domain architecture with differences in length, number of disulfide bonds, and secondary structure. Furthermore, few of them exhibit variable characteristics like chloride dependent activity, the presence of N-terminal glutamine residue to protect against proteolytic degradation, and loop variations near the enzyme active site. Conformation of alpha-AI protein could be an essential factor for their specificity and binding affinities towards target alpha-amylase(s). Furthermore, variation into the enzyme binding pocket residues might contribute to differential interactions with inhibitors. General significance: Molecular insights in the interactions between insect alpha-amylases and plant alpha-AI will provide the details of mechanisms assisting the inhibitor specificity. Furthermore, this information will help to design potent and effective alpha-AIs against specific alpha-amylase.
Keywords: Active site; alpha-amylase; alpha-amylase inhibitor; Insect; molecular interactions

Molecular investigation of coleopteran specific alpha-amylase inhibitors from amaranthaceae members - Rane, Ashwini S.; Venkatesh, Varun; Joshi, Rakesh S.; Giri, Ashok P. (International Journal of Biological Macromolecules, 2020)
alpha-Amylase inhibitors (alpha-AIs) target alpha-amylases and interfere with the carbohydrate digestion of insects. Among different classes of alpha-AIs, a knottin-type inhibitor from Amaranthus hypochondriacus (AhAI) was found to be specific against coleopteran storage pests. In this report, we have characterized three previously unidentified knottin-type alpha-AIs from various Amaranthaceae plants namely, Amaranthus hypochondriacus (AhAI2), Alternanthera sessilis (AsAI) and Chenopodium quinoa (CqAI). They contain a signal peptide, pro-peptide, and mature peptide. The mature peptides of the new alpha-AIs shared 68 to 78% identity with AhAI and have highly variable pro-peptide regions. Along with the cystine-knot fold, they showed conservation of reactive site residues. All recombinant alpha-AIs were successfully expressed in their active form and native state using an oxidative cytoplasmic environment. Inhibition studies against various amylases revealed that these inhibitors showed selective inhibition of coleopteran recombinant insect alpha-amylases viz., Tribolium castaneum, and Callosobruchus chinensis. Tribolium castaneum alpha-amylase inhibition potency was highest for AhAI2 (Ki similar to 15 mu M) followed by AsAI (Ki similar to 43 mu M) and CqAI (Ki similar to 61 mu M). Interaction analysis of these inhibitors illustrated that the reactive site of inhibitors make several non-covalent interactions with the substrate-binding pocket of coleopteran alpha-amylases. The selectivity of these inhibitors against coleopteran a-amylases highlights their potential in storage grain pest control. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: alpha-amylase; alpha-amylase inhibitor; Amaranthaceae; Coleoptera; Knottin-type

Molecular characterization of the beta(2)-like octopamine receptor of helicoverpa armigera - Gujar, Nidhi; Nikte, V, Siddhanta; Joshi, Rakesh S.; Joshi, Manali (Journal of Membrane Biology, 2021)
Helicoverpa armigera is a devastating polyphagous and cosmopolitan crop pest. There are reports of this insect being resistant to a variety of pesticides raising concern worldwide. The Octopamine (OA) binding beta(2)-like receptor (OAR), a GPCR, is widely distributed in the nervous system of the insect and plays essential roles in the physiology and development and thus is an important target for insecticides. Yet, the molecular characterization of the H. armigera OAR (HarmOAR) and rational design of compounds based on this receptor is lacking. As a first step, we performed multiple sequence alignment of all insect OARs, which revealed that the sequences contained all conserved class A GPCR motifs. Phylogenetic studies showed clade-specific variations in the protein sequences primarily arising owing to differences in the ICL3 loop region. Further, a structural model of HarmOAR was built using the inactive human beta(2)AR as a template. 0.9 mu s atomistic simulations revealed conserved inter helical contacts and water molecules of HarmOAR. The detailed binding of octopamine was studied using molecular docking and 0.3 mu s atomistic simulations. Twenty-two insecticides active against octopamine receptors of other insects were compiled and docked to HarmOAR followed by rescoring with binding free energies to prioritize them for H. armigera. Our study suggests alpha-terpineol to be a good candidate as an insecticide or insect repellent for Helicoverpa armigera.
Keywords: docking; Helicoverpa armigera; Insecticides; molecular dynamics; Octopamine receptor; Phylogeny

Molecular investigation of glycated insulin-induced insulin resistance via insulin signaling and AGE-RAGE axis - Walke, Prachi B.; Bansode, Sneha B.; More, Nikita P.; Chaurasiya, Arvindkumar H.; Joshi, Rakesh S.; Kulkarni, Mahesh J. (Biochimica ET Biophysica Acta-Molecular Basis of Disease, 2021)
Hyperglycemic condition in diabetes promotes glycation of various plasma proteins including insulin. Glycation of insulin has been reported to reduce its biological activity. Reduced biological activity of glycated insulin could be either due to reduced affinity for the insulin receptor and impaired insulin signaling, or it can act as a ligand for the receptor for advanced glycation end products (RAGE) and activates oxidative stress and pro-inflammatory pathways leading to insulin resistance. This study investigates the effect of glycated insulin on both insulin and RAGE signaling. Glycated insulin treatment to Chinese hamster ovary (CHO-IR-GLUT4) cells stably expressing insulin receptor (IR) and glucose transporter fused with a green fluorescent protein (GLUT4-GFP) resulted in the impairment of insulin signaling, as the phosphorylation of IR and AKT significantly reduced, which affected GLUT4 translocation and glucose uptake. Moreover, it also activated RAGE signaling as observed by increased expression of NADPH oxidase accompanied by an increase in reactive oxygen species (ROS). Immunofluorescence study indicated the translocation of NF-kappa B to the nucleus upon treatment of glycated insulin. This was associated with increased RAGE expression, Caspase 3, and cell death. Downregulation of RAGE with the losartan treatment restored the impaired insulin signaling and glucose uptake. Additionally, in silico study demonstrated that glycated insulin has reduced binding affinity to insulin receptor and increased binding affinity to RAGE. Overall, this study demonstrates the role of glycated insulin in exacerbating insulin resistance by impairing insulin signaling as well as stimulating AGE-RAGE signaling.
Keywords: AGE; Diabetes; Glycation; Hyperglycemia; insulin; RAGE

Mechanistic insights in the role of trehalose transporter in metabolic homeostasis in response to dietary trehalose - Chaudhari, Bhagyashri Y.; Nichit, Vikram J.; Barvkar, Vitthal T.; Joshi, Rakesh S. (G3-Genes Genomes Genetics, 2026)
Trehalose is the major sugar in insect hemolymph and plays a diverse role. Its level is regulated by the dynamics of biosynthesis and distribution by sugar transporters. The metabolic balance between trehalose synthesis and uptake remains poorly understood, despite its critical role in homeostasis. Here, we examined the role of the putative gut-specific sugar transporter, HaST46, in regulating trehalose levels in Helicoverpa armigera, a model Lepidopteran pest. Analysis of publicly available transcriptomics, proteomics data, and qRT-PCR study suggests that HaST46 showed localization in the posterior midgut and its expression alters in response to dietary contents. The liquid chromatography-mass spectrometry (LC-MS) analysis of HaST46 overexpressing Sf9 cells indicated that trehalose transport is preferred over glucose. HaST46 expression was found to be modulated tissue-specific manner in response to dietary trehalose availability. Furthermore, trehalose synthesis genes were found to be downregulated in the case of a 50 mM trehalose diet. This suggests that a potential increase in exogenous trehalose uptake may attenuate its endogenous synthesis. HaST46 overexpression and silencing lead to altered trehalose levels in the insect, while also having impact on trehalose metabolizing enzymes. Overall, our findings reveal the role of gut predominant sugar transporter, HaST46, in metabolic fine-tuning between exogenous trehalose uptake and endogenous synthesis.
Keywords: gut; Helicoverpa armigera; Metabolism; sugar uptake; transporters; trehalose